Comparison of the effects of silver phosphate and selenium nanoparticles on Staphylococcus aureus growth reveals potential for selenium particles to prevent infection. Issue 2 (30th December 2013) - Chudobova, Dagmar; Cihalova, Kristyna; Dostalova, Simona; Ruttkay‐Nedecky, Branislav; Merlos Rodrigo, Miguel Angel; Tmejova, Katerina; Kopel, Pavel; Nejdl, Lukas; Kudr, Jiri; Gumulec, Jaromir; Krizkova, Sona; Kynicky, Jindrich; et al.
Abstract Interactions of silver phosphate nanoparticles (SPNPs) and selenium nanoparticles (SeNPs) with Staphylococcus aureus cultures have been studied at the cellular, molecular and protein level. Significant antibacterial effects of both SPNPs and SeNPs on S. aureus were observed. At a concentration of 300 μM, SPNPs caused 37.5% inhibition of bacterial growth and SeNPs totally inhibited bacterial growth. As these effects might have been performed due to the interactions of nanoparticles with DNA and proteins, the interaction of SPNPs or SeNPs with the amplified zntR gene was studied. The presence of nanoparticles decreased the melting temperatures of the nanoparticle complexes with the zntR gene by 23% for SeNPs and by 12% for SPNPs in comparison with the control value. The concentration of bacterial metallothionein was 87% lower in bacteria after application of SPNPs (6.3 μg mg−1 protein) but was increased by 29% after addition of SeNPs (63 μg mg−1 protein) compared with the S. aureus control (49 μg mg−1 protein). Significant antimicrobial effects of the nanoparticles on bacterial growth and DNA integrity provide a promising approach to reducing the risk of bacterial infections that cannot be controlled by the usual antibiotic treatments.